Blogs and bloggers - Siles González, Ignacio (2019)
This entry discusses the main characteristics of blogs and bloggers and their coevolution since the start of blogging in the 1990s. Blogs are a kind of website that can be used to present introspective ruminations or an overview of daily events. A blog can serve as an instrument for political mobilization, a journalistic endeavor, an open-ended literary project, or a means for constant exhibition of the self, and in some cases combines more than one of these functions. However, there is little agreement about what features make a blog a blog. Most authors emphasize features such as the frequent publication of content, a reverse chronological order to display blog posts, and archives of previous posts.